Extended Selective Encryption of H.264/AVC (CABAC)- and HEVC-Encoded Video Streams - Boyadjis, Benoit; Bergeron, Cyril; Pesquet-Popescu, Beatrice; Dufaux, Frederic (IEEE transactions on circuits and systems for video technology, 2017)
This paper proposes an extended selective encryption (SE) method for both H.264/advanced video coding (AVC) (CABAC) and High Efficiency Video Coding (HEVC) streams, addressing the main security issue that SE is facing: content protection, related to the amount of information leakage through a protected video. Our contribution is the improvement in the visual distortion induced by SE approaches. Previous works on both H.264/AVC (CABAC) and HEVC limit encryption to bins treated by one specific mode of CABAC-its bypass mode-which has the advantage of preserving the overall bitrate, we propose here to also rely on the encryption of the more widely used mode of CABAC-its regular mode. This allows encryption of a major codeword for video reconstruction, the prediction modes for intra blocks/units. Disturbing their statistics may cause bitrate overhead, which is the tradeoff for improving the content security level of the SE approach. A comprehensive study of this compromise between the improvement in the scrambling efficiency and the undesirable aftereffects is presented in this paper, and a specific security analysis of the proposed CABAC regular mode encryption is conducted.